Relationship between rest-activity rhythms and cardiorespiratory fitness in middle-aged workers: a cross-sectional study with non-parametric analysis using accelerometers worn on the thigh - Jaehoon Seol; Rina So; Fumiko Murai; Tomoaki Matsuo (BMC, 2024)
Abstract Background Rest-activity rhythms are directly related to health risks, but there are limited objective methods to assess them. This study aimed to investigate the relationship between rest-activity rhythms and cardiorespiratory fitness (CRF) in middle-aged workers. Methods Peak oxygen uptake was measured on a treadmill to assess CRF in 254 middle-aged workers who were divided into low, medium, and high-CRF groups based on tertiles. Participants were asked to wear an accelerometer (activPAL) on their thighs for 1 week, and the logarithmically transformed acceleration data were used for the analysis of a 24-hour rest-activity rhythm. Sex, age, body mass index, occupation, smoking status, and alcohol consumption were used as covariates in Model 1, with Model 2 also including walking count on non-workdays. Repeated measures analysis of variance was used to compare time course of rest-activity rhythms changes on workdays between groups, and post-hoc tests were conducted using Bonferroni's correlation. Results Higher CRF correlated with increased physical activity. In model 1, higher CRF showed improved interdaily stability, but the significant difference disappeared in model 2 after adjusting for non-workday walking counts. A time-course group comparison showed that the high group had significantly higher activity levels than those of the low group from 6:00 to 8:59 and 17:00 to 17:59 and the medium group from 6:00 to 7:59 and 19:00 to 19:59. Conclusions Workers who have better rest-activity rhythms and engage in higher levels of physical activity on workdays tend to have higher CRF levels. Regular daily routines, influenced by physical activity during holidays, can positively impact cardiopulmonary endurance.